Assessing the Nâzir Waqf’s Professionalism of Pondok Modern Darussalam Gontor (PMDG) from an Islamic Perspective - Zahro', Khurun'in; Zarkasyi, Hamid Fahmy; Roini, Winda; Cahyo, Eko Nur; Wibisono, Vina Fithriana (al-'adalah, 2025)
This study examines the professionalism of nâzir waqf (endownment administrators) at Pondok Modern Darussalam Gontor (PMDG) in Islamic Boarding School located in Gontor, Ponorogo, West Java, in managing waqf assets. The goal is to obtain an overview of how Islamic principles are applied as a standard of professionalism in waqf governance to improve the community’s economic welfare. This study uses a qualitative approach with a case study method. Data were collected through direct observation, semi-structured interviews, and documentation, applying the triangulation method to ensure data validity. Data analysis follows the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing or verifying conclusions. The results of the study show that although the modern professionalism framework often adopts Western professionalism indicators, in fact, long before the emergence of Western theories, Islam already had the same concept rooted in ‘amal (action), itqân (diligence), and ihsân (goodness). These concepts differ both epistemologically and axiologically. A professional nâzir at PMDG is expected to embody the qualities of shiddîq (honesty), amânah (trustworthiness), tablîgh (effective communication), and fatânah (intelligence). He is also expected to act as a manager, administrator, evaluator, leader, supervisor, innovator, and motivator. This study offers a theory-and practice-based model of waqf management professionalism for developing Islamic philanthropic institutions that align governance practices with sharia principles and modern management standards.